Charakter prawny postępowania przed Urzędem Ochrony Konkurencji i Konsumentów - Sachajko, Marek; Żółtko, Marek (Wydział Prawa i Administracji UAM, 1996)
The July 24, 1990 Act on counteraction against monopolistic practices (Antitrust law) was enacted with aim to guarantee a development of competition, protection of economic entities exposed to monopolistic practice, and protection of the consumers'interest. In this act there are regulated both substantive and procedural matters. The anti-trust procedure before the Office has its specific characteristics which are quite different from the general principles of administrative procedure. Provided above analysis of laws, judicial decisions, and legal literature allowed to show all particular, different points of the procedure before the Office where there are, inter alia, ways to start the procedure, question of standing, oneinstance process, and also a different regulation of recourse.
Proceedings before the National Office for Protection of Competitiveness and Consumers